Navigating the challenges in the transfer between experiential and formal learning in entrepreneurship - Peura Kirsi; Aaltonen Satu (Opetus-, kasvatus- ja koulutusalojen säätiö – OKKA-säätiö sr., 2022)
This study focuses on recognition of prior learning and the accreditation of learning demonstrated in some other manner, and investigates how university teachers accept, resist and negotiate transfer between experiential and formal learning in entrepreneurship. This is done in order to add new knowledge in this under-theorized area and to provide insight about recognition and accreditation of learning that still remain underutilized practices in entrepreneurship. Through discursive approach, the study analyzes personal and group interviews done in 2018-2019 with 56 teachers from 24 Finnish universities. According to the analysis, the teachers mobilise three main discourses when rationalizing the applicability of practices related to recognition and accreditation of learning in entrepreneurship: ‘good teacherhood’, ‘disciplinary’ and ‘university’ discourse. The findings highlight, that recognition and accreditation of learning are not merely assessment-based practi ces. Instead, they challenge the teachers’ ideas about learning, university’s role and the epistemic questions in entrepreneurship. Accordingly, universities should engage teachers in broader discussion about recognition and accreditation of learning, when aiding their adoption in universities. Keywords: recognition of prior learning, RPL, accreditation of learning, studification, entrepreneurship, higher education, discourse analysis, universities.